A Theory of Conveyors - Kwo, T. T. (Management Science, 1958)
The common loop overhead conveyor linking two manufacturing process areas is studied as a mechanism for transforming the output flow of one area into the input flow of the other. The variables relevant to a smooth transformation of flows and their inter-relationships are explored. Findings are formulated into three principles. On the conveyor operation problem, distinguished from the design problem, two methods of simulation are developed and practical suggestions advanced for use in feasibility and optimality considerations. A fundamental observation is that a conveyor is part of a dynamic system, hence information on the connected areas is essential to its smooth operation.